Co-mn-based double-enzyme catalytic activity nanometer film with cycle stability and preparation method and application thereof

CN122999217APending Publication Date: 2026-10-30JIANGSU UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610834011.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-10
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]发明目的:本发明的目的是解决现有粉末钴锰纳米酶易团聚、连续反应中活性组分易流失、难以从体系中分离回收而无法重复使用的技术问题,提供一种可重复利用、具备循环稳定性的Co-Mn基双酶催化活性纳米薄膜,还提供上述Co-Mn基双酶催化活性纳米薄膜的制备方法和应用

Benefits of technology

[0020](1)优异的循环稳定性和可重复使用性:本发明以50 V制备的AAO为模板,通过原位生长将钴锰纳米酶牢固锚定在70-80 nm的孔道中,多次连续反应循环后仍保持稳定的双酶催化活性,有效防止了纳米颗粒的团聚和活性流失。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999217A_ABST
    Figure CN122999217A_ABST
Patent Text Reader

Abstract

The application discloses a Co-Mn-based double-enzyme catalytic activity nanometer film with cycle stability and a preparation method and application thereof. A hierarchical three-dimensional flower cluster-shaped cobalt-manganese composite metal oxide (MMO) nanometer enzyme assembled by two-dimensional ultrathin nanometer sheets is in-situ loaded in an anodic aluminum oxide (AAO) tube hole prepared through anodic oxidation, and a film is prepared by using the AAO template. The film can maintain stable activity after multiple continuous cycles, and moderate pore diameter can improve double-enzyme catalytic activity of the obtained film. The CoMn MMOs@AAO film prepared by the application not only fundamentally prevents agglomeration of nanometer particles and loss of active components, but also has high sensitivity detection and degradation performance which is equivalent to or even better than that of powder, and can be used for detection of phenolic pollutants, and has wide application prospects in the field of environmental monitoring and management.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a Co-Mn-based dual-enzyme catalytic active nanofilm, particularly to a Co-Mn-based dual-enzyme catalytic active nanofilm with cycling stability, and also to a method for preparing and applying the aforementioned Co-Mn-based dual-enzyme catalytic active nanofilm. Background Technology

[0002] Phenolic compounds (especially catechol and hydroquinone), as highly toxic and recalcitrant structural isomers widely emitted in the chemical, pharmaceutical, and manufacturing industries, exhibit extremely high environmental mobility, posing a serious threat to ecosystems and human health. Currently, traditional chromatographic and spectroscopic detection methods require expensive instruments and specialized personnel, while conventional electrochemical sensors face complex sample pretreatment processes. Therefore, developing robust, highly sensitive, and efficient detection and degradation platforms has become an urgent environmental need. In recent years, cobalt-manganese (CoMn) bimetallic nanozymes have demonstrated significant advantages in the field of multi-enzyme biomimetic catalysis due to their internal electron transfer acceleration mechanism and abundant multivalent redox properties. However, existing powdered cobalt-manganese nanozymes have three major fatal flaws in continuous liquid-phase reactions and practical applications: (1) Powdered nanoparticles are prone to spontaneous aggregation, resulting in insufficient exposure of surface active sites; (2) In continuous liquid-phase catalytic reactions, active components are prone to severe leaching and loss, leading to gradual signal degradation; (3) Powdered catalysts are difficult to physically separate and recover from the reaction system, making them unusable. This not only increases application costs but also greatly limits their feasibility in long-term environmental monitoring.

[0003] To address mass transfer limitations and catalyst recovery issues, loading nanocatalysts onto membrane surfaces or within pores has proven to be a viable strategy. Anodized alumina (AAO) templates, with their highly ordered vertical porous nanochannels and precisely tunable pore sizes, as disclosed in the literature “Yang G, Qian Y, Wang L, et al. Advanced Janus membrane (MXene / CoAl-LDH) for efficient asymmetric ion transport and nanofluidic energy harvesting[J]. Nano Energy, 2023, 118: 108972”, are an ideal macroscopic support substrate. Traditional loading methods mainly include two types of specific operations and have inherent conditions that lead to the above-mentioned technical defects: one is physical impregnation coating or vacuum filtration, which is defective because it essentially relies only on physical adsorption such as weak van der Waals forces or electrostatic attraction. The active particles are very easy to randomly agglomerate on the outer surface and at the pore opening, and cannot penetrate into the confined pores. Under the fluid shear force of continuous liquid phase scouring, large-scale peeling and loss of active components are very likely to occur. The second is the traditional interface-free in-situ hydrothermal growth method, which is defective because it lacks precise control of interface nucleation kinetics. The crystal nuclei in the reaction system tend to spontaneously and homogeneously nucleate and grow in the solution phase, rather than undergoing directional heterogeneous nucleation on the porous honeycomb wall of AAO. This results in extremely uneven colonization of the catalyst on the inner wall of the channel and the formation of a loose and disordered accumulation layer on the outer surface of the membrane.

[0004] Therefore, there is an urgent need to develop a macroscopically integrated nanozyme device that is firmly integrated, structurally stable, reusable, and has cycle stability, in order to overcome the technical bottleneck of powder catalysts in environmental monitoring and remediation. Summary of the Invention

[0005] Purpose of the invention: The purpose of this invention is to solve the technical problems of existing powdered cobalt-manganese nanoenzymes being prone to agglomeration, easy loss of active components in continuous reactions, and difficulty in separating and recovering them from the system, thus making them unusable. The invention provides a reusable Co-Mn-based dual-enzyme catalytic active nanofilm with cycle stability, and also provides a method for preparing the above-mentioned Co-Mn-based dual-enzyme catalytic active nanofilm and its applications.

[0006] Technical solution: The Co-Mn-based dual-enzyme catalytic active nanofilm with cycle stability of the present invention includes an AAO template substrate and a three-dimensional flower-like cobalt-manganese nanoenzyme grown in situ on the inner wall of its pores; the three-dimensional flower-like cobalt-manganese nanoenzyme exhibits a hierarchical three-dimensional structure assembled from two-dimensional ultrathin nanosheets cross-linked together; the Co-Mn-based dual-enzyme catalytic active nanofilm has excellent cycle stability, and after more than 10 consecutive reaction cycles, it still retains more than 90% of the oxidase and peroxidase activities, and there is no significant loss of catalytic active components.

[0007] The aforementioned Co-Mn-based dual-enzyme catalytically active nanofilm with cycle stability was prepared by controlled hydrothermal growth and calcination using an anodic alumina template. The preparation method includes the following steps:

[0008] (1) Preparation of anodic aluminum oxide AAO template: After the aluminum alloy substrate is mechanically polished with sandpaper and electrochemically polished in sequence, it is anodized in phosphoric acid solution to obtain an AAO template with a highly ordered honeycomb porous structure with a pore size of 70-80 nm.

[0009] (2) Controllable hydrothermal growth of confined pore morphology: Cobalt nitrate hexahydrate and manganese nitrate hexahydrate were dissolved in deionized water, and urea and ammonium fluoride were added as interfacial binders. The mixture was stirred evenly to obtain a mixed precursor solution. The AAO template was immersed in the precursor solution, and the hydrothermal reaction caused the three-dimensional flower cluster cobalt manganese nanozyme assembled from two-dimensional ultrathin nanosheets to be uniformly filled and firmly anchored to the inner wall of the pores of the AAO template.

[0010] (3) Calcination treatment: The AAO template after hydrothermal reaction is washed alternately with deionized water and anhydrous ethanol, dried under vacuum and then calcined to obtain the Co-Mn-based dual enzyme catalytic active nanofilm CoMn MMOs@AAO with cycle stability.

[0011] In step (1), the anodic oxidation treatment is carried out in a 250-300 g / L phosphoric acid solution with a lead plate as the cathode, using a constant voltage of 50V for 10-20 min; the mechanical polishing is performed using 1500-mesh SiC sandpaper; the electrochemical polishing is carried out in a mixture of phosphoric acid and ethanol with a volume ratio of 4:1 to 1:4, preferably 3:2; the current density is 20 A / dm³. 2 .

[0012] In step (2), the molar ratio of cobalt nitrate hexahydrate and manganese nitrate hexahydrate in the precursor fluid is 3:1 to 1:3, preferably 3:1, and the total metal ion concentration is 0.4-0.5 mol / L. Cobalt ions can be replaced by cobalt salts such as cobalt sulfate, cobalt chloride, and cobalt acetate, and manganese nitrate can be replaced by manganese salts such as manganese acetate and manganese chloride. Ethanol and ethylene glycol can be added to the solvent.

[0013] In step (2), the hydrothermal reaction temperature is 110-130 ℃ and the time is 10-14 h.

[0014] In step (3), the number of alternating washes is greater than 3, the drying conditions are 50-80 ℃ for 6-8 h, and the calcination conditions are 400-500 ℃ in air at a rate of 2-10 ℃ / min for 2-3 h.

[0015] The aforementioned Co-Mn-based dual-enzyme catalytically active nanofilms with cycling stability are used in the colorimetric real-time detection of phenolic pollutants, namely, the colorimetric detection of phenolic pollutants in environmental monitoring and water remediation.

[0016] The phenolic pollutants include catechol and hydroquinone. The detection limit of the membrane for catechol is 0.18 μM and the detection limit for hydroquinone is 0.26 μM.

[0017] Invention Principle: The Co-Mn@AAO nanofilm with cycling stability of the present invention exhibits a hierarchical three-dimensional structure (not a single solid flower morphology) composed of cross-linked two-dimensional ultrathin nanosheets. This hierarchical structure is uniformly distributed within the honeycomb porous channels of AAO. Due to the strong bond between the nanoenzyme and the pore walls of AAO, and the effective prevention of nanoparticle aggregation by the pore structure of AAO, excellent cycling stability is demonstrated. After multiple consecutive reaction cycles, the oxidase and peroxidase activities of the film remain highly stable, effectively avoiding the shortcomings of traditional powder catalysts such as short lifespan and easy deactivation. When applied to the detection of phenolic pollutants, it fully retains the intrinsic catalytic activity of the three-dimensional flower-like cobalt-manganese nanoenzyme, possessing detection and degradation performance comparable to or even better than that of powder catalysts. Simultaneously, it solves the fatal flaw of powder catalysts' inability to be reused. The detection limit for catechol (CC) reaches 0.18 μM, and the detection limit for hydroquinone (HQ) reaches 0.26 μM.

[0018] In the preparation steps of this invention, the use of ammonium fluoride as a binder plays a crucial role. The introduction of ammonium fluoride can effectively regulate the local chemical microenvironment of the reaction system, promote the uniform nucleation and firm anchoring of the cobalt-manganese precursor on the inner wall of the AAO channels, significantly enhance the interfacial binding force between the nanozyme and the carrier, and fundamentally prevent the loss and peeling of active components during continuous recycling.

[0019] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:

[0020] (1) Excellent cycle stability and reusability: The present invention uses AAO prepared at 50 V as a template to firmly anchor cobalt manganese nanozymes in 70-80 nm pores through in-situ growth. After multiple continuous reaction cycles, it still maintains stable dual-enzyme catalytic activity, effectively preventing the aggregation of nanoparticles and loss of activity.

[0021] (2) High catalytic performance: The obtained film completely retains the intrinsic catalytic activity of the three-dimensional flower cluster cobalt manganese nanozyme. Its hierarchical three-dimensional nanosheet structure provides abundant oxygen vacancies and multivalent electron transfer network, which significantly accelerates interfacial electron transfer and superoxide radical generation.

[0022] (3) Easy to separate and industrial application: The nanoscale powder is transformed into a macroscopic integrated thin film device, which realizes the easy physical separation of the catalyst and the reaction system, greatly reducing the operating cost of long-term environmental monitoring and water body remediation. Attached Figure Description

[0023] Figure 1 SEM image of the AAO template prepared by anodizing at 20V;

[0024] Figure 2 SEM image of CoMn nanozymes loaded onto an AAO template prepared at 20V;

[0025] Figure 3 The graph shows the stability of peroxidase activity of the CoMn@AAO nanoenzyme film.

[0026] Figure 4 Linear fitting plot for the detection of catechol by CoMn nanozyme membrane;

[0027] Figure 5 SEM image of rod-shaped CoMn nanozyme;

[0028] Figure 6 This is a SEM image of a spherical CoMn nanozyme. Detailed Implementation

[0029] The technical solution of the present invention will be further described below with reference to the accompanying drawings.

[0030] Example 1

[0031] The Co-Mn-based dual-enzyme catalytically active nanofilm with cycle stability of the present invention is prepared by the following steps:

[0032] (1) Preparation of AAO template: A 6061 aluminum alloy sample (10 mm × 10 mm × 2 mm) was mechanically polished using 1500-mesh SiC sandpaper. Subsequently, electrochemical polishing was performed in a mixture of phosphoric acid and ethanol (volume ratio 3:2), with the aluminum alloy as the anode and the 316 stainless steel plate as the cathode, at a current density of 20 A / dm³. 2 Subsequently, anodic oxidation was performed in a 300 g / L phosphoric acid solution using a lead plate as the cathode at a constant voltage of 50 V to obtain a highly ordered honeycomb AAO template with a pore size of approximately 70-80 nm.

[0033] (2) In-situ hydrothermal loading: 24 mmol cobalt nitrate hexahydrate and 8 mmol manganese nitrate hexahydrate were dissolved in 70 mL of deionized water (Co / Mn molar ratio of 3:1), urea was added to make the final concentration 0.2 mol / L, and 38 mmol ammonium fluoride was added as a binder. The mixture was stirred vigorously to form a homogeneous solution. The 50 V AAO template obtained in step (1) was placed in a polytetrafluoroethylene liner, the mixture was poured in, and the reaction was carried out at 120 °C for 12 h.

[0034] (3) Post-treatment: After natural cooling, the composite film was rinsed alternately with deionized water and anhydrous ethanol, vacuum dried at 60 °C for 6 h, and finally calcined in air at 400 °C for 2 h to obtain a Co-Mn-based dual-enzyme catalytic active nanofilm with cycle stability, denoted as 50 V AAO@CoMn film.

[0035] Comparative Example 1

[0036] A Co-Mn-based dual-enzyme active nanofilm was prepared using a method similar to that in Example 1, except that the anodic oxidation voltage in step (1) was adjusted to 20 V, while all other steps remained the same. The resulting film was denoted as 20 V AAO@CoMn. Its SEM image is shown below. Figure 1 As shown, the pore size of the narrow channel is relatively small, approximately 50 nm.

[0037] Comparative Example 2

[0038] A Co-Mn-based dual-enzyme active nanofilm was prepared by adjusting the anodic oxidation voltage in step (1) to 60 V, while the other steps remained the same. The resulting film was denoted as 60 V AAO@CoMn. Its pore size reached about 120 nm, which led to excessive etching and partial collapse of the pore walls.

[0039] Comparative Example 3

[0040] An Al@CoMn thin film, which is an Al@CoMn thin film without anodizing, is prepared by only mechanical polishing and electrochemical polishing in step (1) and without anodizing to obtain an aluminum alloy substrate. The substrate is then directly subjected to the same in-situ hydrothermal loading in step (2) and post-treatment in step (3).

[0041] Comparative Example 4

[0042] A method for preparing Co-Mn-based dual-enzyme active nanofilms, compared with Example 1, involves replacing the solvent in step (1) with anhydrous ethanol, while keeping the other steps the same. Characterization results show the formation of a one-dimensional rod-like structure, such as... Figure 5 As shown, it is impossible to fill the AAO channels, and the surface is severely aggregated.

[0043] Comparative Example 5

[0044] A method for preparing Co-Mn-based dual-enzyme active nanofilms, compared with Example 1, involves replacing the solvent in step (1) with ethylene glycol, while keeping the other steps the same. Characterization results show the formation of dense spherical aggregates, such as... Figure 6 As shown, it is impossible to enter the AAO channel.

[0045] Stability testing and structural comparative analysis:

[0046] Through observation Figure 2 SEM characterization results revealed that the CoMn material exhibited severe random aggregation and significant surface cracking on the film surfaces prepared in Comparative Example 3 (without anodizing) and Comparative Example 1 (20 V narrow pores), resulting in extremely poor interfacial adhesion. In Comparative Example 2 (60 V collapsed pores), an irregular dense layer formed on the surface, making it difficult for the precursor to penetrate. However, the optimal embodiment 1 of this invention (50 V AAO template) provided an ideal nanoconfined environment, with three-dimensional flower-like nanosheets of CoMn uniformly anchored on the pore walls.

[0047] After 5-6 consecutive reaction cycles, the results are as follows: Figure 3 As shown: The 50 V AAO@CoMn film prepared in Example 1 exhibits the highest and most stable oxidase (OXD) and peroxidase (POD) catalytic absorbance signals, proving that it effectively overcomes the defect of easy loss of powder catalyst and has excellent cycle stability.

[0048] CoMn@AAO films for colorimetric detection of catechol (CC)

[0049] The CoMn@AAO thin film prepared in this invention fully retains the intrinsic catalytic activity of the three-dimensional flower-like cobalt-manganese nanozyme, thus possessing detection and degradation performance comparable to or even superior to that of the powder, while avoiding the fatal flaw of the powder's inability to be reused. Thin film devices and different concentrations of CC were introduced under optimal detection conditions (NaAc-HAc buffer at pH = 4.0, 0.56 mM TMB, 50 μM H2O2). The addition of CC caused a decrease in the system's absorbance (652 nm). Figure 4 As shown, it exhibits excellent linearity (R² = 0.9954) in the concentration range of 0–70 μM, with a detection limit as low as 0.18 μM.

[0050] CoMn@AAO films were used for the colorimetric detection of hydroquinone (HQ).

[0051] The CoMn@AAO thin film prepared in this invention fully retains the intrinsic catalytic activity of the three-dimensional flower-like cobalt-manganese nanozyme. HQ was detected using the same reaction system as described above. The device exhibits a two-stage linear dynamic range: absorbance decreases sharply in the low concentration range of 0–10 μM, while a more gradual linear response is observed in the 10–50 μM range. The system's detection limit for HQ is as low as 0.26 μM, demonstrating high sensitivity and interference-resistant selectivity for accurately identifying phenolic isomers in complex aquatic environments.

Claims

1. A method for preparing a Co-Mn-based dual-enzyme catalytically active nanofilm with cycle stability, characterized in that, The Co-Mn-based dual-enzyme catalytically active nanofilm was prepared by hydrothermal growth of cobalt-manganese precursors on an AAO template followed by calcination, and included the following steps: (1) Preparation of AAO template: After the aluminum alloy substrate was mechanically polished with sandpaper and electrochemically polished in sequence, it was anodized in phosphoric acid solution to obtain an AAO template with a highly ordered honeycomb porous structure with a pore size of 70-80 nm. (2) Preparation of pore-confined precursor: Cobalt nitrate hexahydrate and manganese nitrate hexahydrate were dissolved in deionized water, and urea and ammonium fluoride were added as interfacial binders. The mixture was stirred evenly to obtain a mixed precursor solution. The AAO template was immersed in the precursor solution and hydrothermally reacted to obtain a three-dimensional flower-shaped cobalt-manganese nanozyme assembled from two-dimensional ultrathin nanosheets, which was uniformly filled and firmly anchored to the inner wall of the pores of the AAO template. (3) Calcination treatment: The AAO template precursor obtained after hydrothermal reaction is calcined to obtain the Co-Mn-based dual enzyme catalytic active nanofilm CoMn MMOs@AAO with cycle stability.

2. The preparation method according to claim 1, characterized in that, In step (1), the anodic oxidation process is carried out in a 250-300 g / L phosphoric acid solution with a lead plate as the cathode and a constant voltage of 45-55 V for 10-20 min.

3. The preparation method according to claim 1, characterized in that, In step (1), the mechanical polishing of the anodic aluminum oxide (AAO) template is performed using SiC sandpaper.

4. The preparation method according to claim 1, characterized in that, In step (1), the electrochemical polishing in the preparation of the anodic aluminum oxide (AAO) template is carried out in a mixture of phosphoric acid and ethanol in a volume ratio of 4:1 to 1:

4.

5. The preparation method according to claim 1, characterized in that, In step (2), the molar ratio of cobalt nitrate hexahydrate and manganese nitrate hexahydrate in the precursor liquid for the preparation of the pore-confined precursor is 3:1 to 1:3, and the total metal ion concentration is 0.4-0.5 mol / L.

6. The preparation method according to claim 1, characterized in that, In step (2), the hydrothermal reaction temperature for preparing the pore-confined precursor is 110-130 °C and the time is 10-16 h.

7. The preparation method according to claim 1, characterized in that, In step (3), the calcination conditions for CoMn MMOs@AAO are: heating to 400-500 ℃ in air at 2-10 ℃ / min, maintaining the temperature for 2-3 h, and then naturally cooling to room temperature.

8. A Co-Mn-based dual-enzyme catalytically active nanofilm with cycle stability prepared by the method of claim 1, characterized in that, The film includes an AAO template substrate and a three-dimensional flower-shaped cobalt-manganese nanozyme grown in situ on the inner wall of its pores; the three-dimensional flower-shaped cobalt-manganese nanozyme is a hierarchical three-dimensional structure assembled by cross-linking two-dimensional ultrathin nanosheets.

9. The application of the Co-Mn-based dual-enzyme catalytically active nanofilm with cycling stability as described in claim 8 in the instantaneous colorimetric detection of phenolic pollutants.

10. The application according to claim 9, characterized in that, The dual-enzyme catalytic activity is the dual-enzyme catalytic activity of oxidase and peroxidase, and the phenolic pollutant is a diphenol, including catechol and hydroquinone.